Bridging therapy during delayed definitive radiotherapy in locally advanced head and neck squamous cell carcinoma: a prospective randomized study comparing induction TPF chemotherapy with oral metronomic chemotherapy - Ipsita Palui; Abhishek Basu; Sayani Poddar; Koushik Chatterjee (International Journal of Research in Medical Sciences, 2026)
Background: Prolonged waiting periods before definitive radiotherapy remain a major challenge in the management of locally advanced head and neck squamous cell carcinoma (LA-HNSCC), particularly in resource-constrained healthcare settings. Bridging systemic therapy during this interval may help maintain disease control until definitive radiotherapy can be initiated. The aim of the study was to compare the efficacy and safety of induction docetaxel, cisplatin, and 5-fluorouracil (TPF) chemotherapy with oral metronomic chemotherapy (OMCT) as bridging treatment in patients with LA-HNSCC experiencing unavoidable delays before definitive radiotherapy. Methods: A prospective randomized study was conducted in the Department of Radiotherapy, IPGME&R and SSKM Hospital, Kolkata, India, between February 2020 and November 2022. Sixty patients with biopsy-proven stage III-IVB LA-HNSCC were randomized to receive either two cycles of induction TPF chemotherapy (Arm A) or oral metronomic chemotherapy comprising weekly methotrexate and twice-daily celecoxib (Arm B) while awaiting definitive radiotherapy. Tumour response, treatment-related toxicities, disease-free survival (DFS), overall survival (OS), and quality of life were assessed. Survival outcomes were estimated using the Kaplan-Meier method. Results: Baseline demographic and clinicopathological characteristics were comparable between the two treatment groups. Induction TPF chemotherapy achieved significantly higher objective tumour response before radiotherapy and superior complete response rates following treatment compared with OMCT. Disease-free survival was significantly longer in the TPF arm, whereas overall survival was comparable between the two groups during the study period. Conclusions: Induction TPF chemotherapy provided superior tumour response and disease-free survival compared with oral metronomic chemotherapy.